PROFIL DAN MOTIVASI ENTREPRENEUR WANITA DI YOGYAKARTA* - Indarti, Nurul; Wulandaru, Diah Retno (Journal of Indonesian Economy and Business, 2003)
This study aims to describe entrepreneurial motivation of women entrepreneurs in Yogyakarta. Previous studies paid great attention to the idea that people are motivated to use their jobs as mechanisms for satisfying their needs.Research that explored gender issue is still growing debate in the area of management. This study questions how four psychological needs influence women entrepreneurs. Survey approach was conducted to answer such research questions.This study uses 96 respondents representing 63% response rate.Findings revealed that young women entrepreneurs were strongly motivated by achieving performance, followed by affiliation, autonomy and dominance. It also showed that women entrepreneurs had lower need for affiliation and higher need for dominance than women employees had. This results imply that recognition or appreciation and adequate resources should be available to support women entrepreneurs to fulfill their needs for achievement and to exercise their leadership style.Keywords: women entrepreneur, motivation, need for achievement, need for affiliation, need for autonomy, need for dominance.